2006
DOI: 10.1111/j.1399-5618.2006.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of suicide attempt history in bipolar disorder: a stress‐diathesis perspective

Abstract: Aggressive traits and early treatment of mood disorders, especially major depressive episodes, are potential targets for suicide prevention in bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 51 publications
7
53
2
2
Order By: Relevance
“…This was not explained by years ill, lifetime number of major depressive episodes, or BD-I vs. II/NOS subtype. Hostility was associated with suicide attempt risk, consistent with previous reports from our group (Grunebaum et al, 2006;Oquendo et al, 2000). Reasons for living appeared to be an important protective factor.…”
Section: Discussionsupporting
confidence: 81%
“…This was not explained by years ill, lifetime number of major depressive episodes, or BD-I vs. II/NOS subtype. Hostility was associated with suicide attempt risk, consistent with previous reports from our group (Grunebaum et al, 2006;Oquendo et al, 2000). Reasons for living appeared to be an important protective factor.…”
Section: Discussionsupporting
confidence: 81%
“…34,42 Lifetime aggressiveness is reported to be also higher in previous attempters. 30,55 Impulsivity seems to play a different role in bipolar patients. In other psychiatric conditions (e.g., major depression), impulsivity is associated with suicide attempts.…”
Section: ) Rapid Cyclingmentioning
confidence: 97%
“…42 Grunebaum et al evaluated 96 patients with bipolar disorder and observed that the percentage of attempters reporting a history of physical or sexual abuse was twice as much as among non-attempters, although this variable was not retained in the regression analysis. 55 One interesting point about physical and sexual abuse is that in a family study the rates of childhood abuse were higher in probands with a family history of suicidal behavior 79,80 and a history of sexual abuse in either the parents 81 or the offspring predicted suicidal behavior in offspring. 79 9) Family history Several family studies have found that the higher risk of suicidal behavior conferred holds true even after controlling for the effects of psychiatric disorders.…”
Section: ) Rapid Cyclingmentioning
confidence: 99%
See 2 more Smart Citations